Assessment of Conductivity-Temperature-Depth via multi-criteria approach: Regret theory based model on the pythagorean fuzzy environment. (15th December 2022) - Zhang, Chonghui; Yu, Chenhong; Yuan, Lingjing; Balezentis, Tomas; Zeng, Shouzhen
Abstract: Sustainable development of marine economy requires strengthening the marine environmental monitoring and management. Conductivity-Temperature-Depth (CTD) realises multi-dimensional monitoring of marine environment by measuring the traits of seawater. To further promote real-time online marine monitoring, conducting a robust assessment of CTD equipment is a primary task for capacity building. In this paper, to evaluate several equipment options, a multiple-criteria decision-making model, based on regret theory and squared-confidence Pythagorean fuzzy hybrid weighted arithmetic and geometric aggregation (SCPFHWAGA) operator is proposed. The SCPFHWAGA operator takes into account the confidence level, which enhances the comprehensiveness of information aggregation. In addition, considering the differences in subjective confidence in equipment use, social network analysis and regret theory are introduced. The evaluation criteria are then designed with the concerns raised before, during and after using the equipment, which reflects the whole process of CTD equipment evaluation more objectively. The case of Zhejiang (China) is analysed. The robustness and validity of the proposed framework are verified by comparing the results with those obtained using other methods. Highlights: Multi-criteria model for sustainable marine resource management is proposed. The case of Zhoushan, China, that can be affected by nuclear contamination is considered. Integrated assessment of the Conductivity-Temperature-Depth equipment. The fuzzy logics allow assessing the traits of equipment and interactions among the experts.